Antibacterial Effect of Chloroform Fraction from Ethanol Extract of Pandan Wangi Leaves (Pandanus amaryllifolius Roxb) - Nur Ismiyati; Ana Mardiyaningsih; Sherly Herdianti (Politeknik Kesehatan Bhakti Setya Indonesia, 2021)
Pandan wangi leaves are often used as a flavoring (corrigen saporis) and an aroma (corrigen odoris). The use of pandan wangi leaves as a food preservative was found in several studies. The content of flavonoid compounds, saponins, polyphenols, tannins, and alkaloids is thought to have antibacterial activity. The purpose of this study was to determine the chloroform fraction of ethanolic extract of fragrant pandan leaves as antibacterial against Staphylococcus aureus and Escherichia coli. The active compounds contained in the chloroform fraction of ethanolic extract of pandan wangi leaves was identified by phytochemical screening test. This research is a true experimental research with posttest only control group design. The antibacterial activity was tested using the agar diffusion method (Test Kirby & Bauer) using the cup - plate technique. The doses used for each extract were 2,000 mg (10mL), 5,000 mg (25mL), and 10,000 mg (50mL). Phytochemical screening test using test tube. The results of the antibacterial activity were analyzed using the Kruskal-Wallis Test and the Mann-Whitney Test. The results showed that the chloroform fraction of the ethanol extract had antibacterial activity against Staphylococcus aureus, but not against Escherichia coli. The chloroform fraction of the ethanol extract in the phytochemical screening test was positive for alkaloids, polyphenols, saponins, and triterpenoids. Keywords: Pandanus amaryllifolius Roxb., Staphylococcus aureus, Escherichia coli, antibacterial, phytochemical screening